2005
DOI: 10.1158/0008-5472.379.65.2
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Targets of Gefitinib

Abstract: Targeted inhibition of protein kinases with small molecule drugs has evolved into a viable approach for anticancer therapy. However, the true selectivity of these therapeutic agents has remained unclear. Here, we used a proteomic method to profile the cellular targets of the clinical epidermal growth factor receptor kinase inhibitor gefitinib. Our data suggest alternative cellular modes of action for gefitinib and provide rationales for the development of related drugs.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(33 citation statements)
references
References 16 publications
0
33
0
Order By: Relevance
“…This cysteine residue has been previously reported to be located next to the highly conserved DFG motif, which in an active kinase state coordinates magnesium ion in the ATP binding site . Interestingly, a structurally similar analog of dacomitinib, FDA-approved EGFR inhibitor gefitinib, has also been demonstrated to target GAK. ,, Additionally, GAK C190 has been recently characterized as a target of a SM1-71, a promiscuous covalent kinase inhibitor …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This cysteine residue has been previously reported to be located next to the highly conserved DFG motif, which in an active kinase state coordinates magnesium ion in the ATP binding site . Interestingly, a structurally similar analog of dacomitinib, FDA-approved EGFR inhibitor gefitinib, has also been demonstrated to target GAK. ,, Additionally, GAK C190 has been recently characterized as a target of a SM1-71, a promiscuous covalent kinase inhibitor …”
Section: Resultsmentioning
confidence: 97%
“…57 Interestingly, a structurally similar analog of dacomitinib, FDA-approved EGFR inhibitor gefitinib, has also been demonstrated to target GAK. 32,58,59 Additionally, GAK C190 has been recently characterized as a target of a SM1-71, a promiscuous covalent kinase inhibitor. 60 Another cysteine residue that was observed to undergo modulation upon treatment with dacomitinib was C218, localized in close proximity to the active site of glycogen synthase kinase-3 beta (GSK3B).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Kinase inhibitors, while being valuable drugs and powerful molecular probes, have been recognized to display widely varying degrees of target selectivity, , which may lead to toxicity or conversely enable repurposing of clinical compounds. , Understanding a kinase inhibitor’s cellular target profile also has important implications for the correct evaluation of its biological effects, as noncanonical targets can either decrease or enhance cellular efficacy and assist in dissecting the wiring maps of the targeted signaling networks.…”
Section: Discussionmentioning
confidence: 99%
“…The T790M mutation was originally identified from patients treated with gefitinib and later found in other patients receiving erlotinib treatment . Clinical studies demonstrated that the gatekeeper mutation (T790M) resulted in a dramatic reduction in therapeutic efficacy of EGFR-selective inhibitors . Recently novel inhibitors are designed to target inhibitor resistant mutants including afatinib and neratinib, both of which have advanced to phase III clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…12 Clinical studies demonstrated that the gatekeeper mutation (T790M) resulted in a dramatic reduction in therapeutic efficacy of EGFR-selective inhibitors. 13 Recently novel inhibitors are designed to target inhibitor resistant mutants including afatinib 14 and neratinib, 15 both of which have advanced to phase III clinical trials.…”
Section: Introductionmentioning
confidence: 99%